Acidic fibroblast growth factor (FGF) from bovine brain: amino-terminal sequence and comparison with basic FGF. - Böhlen, P (1985)
Acidic fibroblast growth factor (FGF) from bovine brain has been isolated by a combination of salt precipitation, ion-exchange chromatography, heparin-Sepharose affinity chromatography and reverse phase h.p.l.c. The amino acid composition of the mitogen is indistinguishable from that of acidic FGF previously purified. The amino-terminal sequence of acidic FGF was established as Phe-Asn-Leu- Pro-Gly-Asn-Tyr-Lys-Pro-Lys-Leu-X-Tyr-X-Ser-Asn-Gly-X-Tyr-Phe-Leu-Arg-Il e-Leu-Pro-Asp-Gly. Acidic FGF is structurally different from basic FGF as judged by mol. wt., amino acid composition and sequence. In vitro biological comparison of the two growth factors indicates that acidic and basic FGFs possess the same intrinsic activities to stimulate the proliferation of aorta, vein or capillary endothelial cells and adrenal cortex cells, but acidic FGF is 30-100 times less potent, depending on the cell type.